Brexit and Tourism : Process, Impacts and Non-Policy - Hall, Derek (Aspects of Tourism, 2020)
This book offers a multidisciplinary, holistic appraisal of the implications of the UK's withdrawal from the European Union (EU) for tourism and related mobilities. It attempts to look beyond the short- to medium-term consequences of these processes for both the UK and the EU. It is divided into four major sections: Context, Tourism Impacts, Implications, and Global Britain? The volume employs case studies to highlight Brexit's ripple effects on tourism, mobilities and immobilities. It will be of interest to researchers, students and policymakers in tourism, European studies, political geography, regional development, international relations and politics.